Car Culture and Masculinity as Resources for Understanding Road Rage - Mabongo, Qhawekazi Khazimla (University of the Witwatersrand, Johannesburg, 2024)
Aggression on the road and aggressive driving are detrimental to other road users. Road rage may be expressed in multiple behaviours on the road such as violence, tailgating, overtaking when it is not safe to do so, and brake checking. This behaviour poses a threat to the lives of people on the road. The objective of this study was to investigate the existence of masculinity and car culture principles in the way men perceived incidents of road rage. Further, the study aimed to understand how the features of masculinity and car culture are presented in the perceptions men had of road rage. The rationale for this study was motivated by the high prevalence of road accidents, where young men were the most vulnerable to road accidents and road fatalities. Aggressive driving behaviour was the focus of this study as young men were identified as the most common culprits of performing behaviours of this nature. The study adopted a socio-cultural approach to road rage and proposed the use of socio-cultural factors, namely masculinity and car culture, as a framework for the exploration of the psychological experiences related to road rage. The data was collected using nine in-depth interviews structured around three vignettes in the form of videos. The interviews were audio recorded and transcribed. Thematic analysis principles stipulated by Braun and Clarke were utilised to guide the analysis and reporting of the data. The findings of this study were intended to inform interventions for violence and road rage by providing a nuanced understanding of the relationship between risk factors and violence as well as providing insight into the underpinning perceptions of road behaviour and, consequently, road accidents. The main findings indicated that the road is a site for social interactions that are informed by the tenets of masculinity and car culture. Both masculinity and car culture intersect and create complex social dynamics between road users. These identities influence the experience of men on the road as they are a lens for perceiving behaviour, and they also influence the behaviour of men on the road. Additionally, the research demonstrated that masculinity and car culture are related and the fundamental characteristic that underlies both concepts is power.
A research report Submitted in fulfillment of the requirements for a Master of Arts in Clinical Psychology, In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: MM2025; SDG-15: Life on land